Systematic Review: Therapeutic Potential of Vitamin E and Coenzyme Q10 in Traumatic Brain Injury (TBI) - I Wayan Tunjung; I Made Putra Biantara (Global Health Science Group, 2025)
Traumatic brain injury (TBI) is one of the major neurological problems with high incidence and disability rates globally. To date, there is no fully effective standard therapy available to treat nerve damage caused by TBI, necessitating new approaches targeting the primary pathophysiological mechanisms, particularly oxidative stress and inflammation. This narrative review aims to explore the therapeutic potential of vitamin E and coenzyme Q10 as neuroprotective agents in TBI. The study was conducted by reviewing literature from various scientific databases, focusing on publications from 2020–2025 that discuss the effects of these two compounds on TBI. Vitamin E, particularly α-tocopherol, acts as a lipophilic antioxidant that protects neuronal cell membranes from lipid peroxidation, suppresses inflammatory responses, and supports neuroplasticity. Coenzyme Q10 functions as a cofactor in the mitochondrial electron transport chain, maintaining ATP production, and possesses strong antioxidant and anti-inflammatory effects. Preclinical studies indicate that supplementation with vitamin E and coenzyme Q10 can reduce oxidative stress biomarkers, improve neurological function, and reduce brain lesion volume and neuronal cell death in animal models of TBI. Clinical data is still limited, but there are indications of benefits as supportive therapy. The combination of these two antioxidants also shows synergistic effects in protecting brain tissue. In conclusion, vitamin E and coenzyme Q10 have significant potential as adjunctive therapies in TBI management, although further clinical trials are needed to confirm their efficacy and safety.